African literary festivals and world literature: from the map to the territory - (:unkn) unknown (My University, 2019)
In an era where cultural festivals multiply, so-called African festivals have spread in Africa, but also outside of the continent, in major cities as well as in little-known villages, for example in provincial France. What are some of their implications and effects in the case of francophone African literature? These events privilege a continental representation of literature, which often reveals itself as problematic when confronted with the complex geographies of the texts and authors represented at these festivals. Using cross-disciplinary methodology, this critical inquiry reads different reallocations of this persistent African matrix through a typology and contemporary examples (Kossi Efoui’s writings, the “Étonnants Voyageurs” and “Plein sud” festivals). As an object of study, festivals bear witness to the necessity of expanding the toolbox of the (world) literary scholar by making use of documentary sources and adopting ethnographic approaches. It reveals a structural tension between an African map and various concrete territories, where local issues matter often more than this continental category, and can affect the form and content of literature itself.
Keywords: African Research